ANÁLISE COMPARATIVA DE DESEMPENHO ESTRUTURAL E VIABILIDADE ECONÔMICA ENTRE CONCRETO ARMADO, ESTRUTURA METÁLICA E MADEIRA: UMA PERSPECTIVA PARA APLICAÇÕES RESIDENCIAIS DE PADRÃO POPULAR (REMUNOM, 2025)
The construction industry seeks to employ innovative and sustainable construction technologies, new construction techniques and efficient construction materials. The aim is to reduce time, cost and resources in the execution of works. The objective of this work was to conduct a comparative study of three construction methods: Reinforced Concrete, Steel Frame and Wood Frame in a popular housing project. The work addressed issues such as sealing methods, thermal and acoustic performance, sustainability, construction time and economic viability of each method presented. To this end, a survey of quantities, construction materials and labor used in the proposed construction methods were presented. The conclusion of this study demonstrates that both Steel Frame and Wood Frame are viable alternatives to reinforced concrete, offering benefits in terms of speed of execution, sustainability and comfort. Although reinforced concrete is valued for its strength, Steel Frame stands out for its agile and safe execution, and Wood Frame for its thermal and acoustic performance. With the qualification of the workforce, these methods can contribute significantly to affordable housing in Brazil..